Study of Phytochemical and Antimicrobial Activities of Waltheria indica - Y., Musa; M., Musah; H., Yerima; N. B., Erena (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
Waltheria indica is used in Nigeria and other parts of the world as traditional medicine for the treatment of several ailments such as skin disease, impotence, malaria, typhoid fever, epilepsy infertility, aches, pains, syphilis, pile, cough, sore throat, gonorrhea and leprosy among others. The extracts of this plant: Aqueous, chloroform and methanolic extract were subjected to both phytochemical and antimicrobial screening. The result of the phytochemical screening showed the occurrence of Flavonoids, Anthraquinones, Saponins, Tannins, Terpenes, Cardiac glycosides and Carbohydrate. But absence of free anthraquinone and phlobatanines.The Antimicrobial activity of the extracts using Agar plate-hole, Nutrient broth and Agar diffusion method. It was found that the plant extracts from both methanol and chloroform were notable to exhibit any reasonable activity while Aqueous extract showed reasonable activity with Escherielia coli and Staphylococcus aureus. These finding, however, support the traditional use of the Waltheriaindica for the treatment of the above mentioned diseases. This is because Aqueous extract is the only extract that show inhibitory effect and similarly the traditional healers uses water for their extraction.